2021
DOI: 10.3390/rs13081515
|View full text |Cite
|
Sign up to set email alerts
|

Maria Basalts Chronology of the Chang’E-5 Sampling Site

Abstract: Chang’E-5 is the first lunar sample return mission of China. The spacecraft was landed in the northwest of the Procellarum KREEP Terrane (43.0576°N, 308.0839°E) on 1 December 2020 and returned 1731 g samples from a previously unvisited region. The landing area has been proposed as one of the youngest mare basalt units of the Moon and holds important information of lunar thermal evolution and chronology. However, the absolute model ages estimated in previous studies are quite different, ranging from 2.07 Ga to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…Xu et al. (2021) obtained an almost identical N (1) value with Wu et al. (2018), and these two studies both measured craters on LROC NAC images for smaller count areas.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Xu et al. (2021) obtained an almost identical N (1) value with Wu et al. (2018), and these two studies both measured craters on LROC NAC images for smaller count areas.…”
Section: Discussionmentioning
confidence: 52%
“…Among these derived N(1) values, Qian et al (2018) reported the smallest values, close to Hiesinger et al (2003) from old Lunar Orbiter image data, while and Qian, Xiao, Wang, et al (2021) updated their results later to around 1.3 × 10 −3 km −2 . Xu et al (2021) obtained an almost identical N(1) value with Wu et al (2018), and these two studies both measured craters on LROC NAC images for smaller count areas. Morota et al (2011) got N(1) values around 1.6 × 10 −3 km −2 for the P58 unit.…”
Section: Crater Sfd Analysis Results: Comparison With Previous Studiesmentioning
confidence: 61%
“…In this paper, pure basalt and mixture are distinguished according to this threshold. It can be seen from Figure 8 that the FeO concentration at the landing site of CE-5 is high, greater than 17.2 wt.%, but there are non-pure basalt materials less than 17.2 wt.% in the surrounding area, which may be ejecta and rays from sharp B, Harding, Copernicus, and Aristarchus [46].…”
Section: Surface Ages Of the Mare Units In The Ce-5 Regionmentioning
confidence: 99%
“…Korovet et al [45] analyzed the samples returned from Apollo and Luna and found that the FeO abundance of mare basalt ranged from 16 to 23 wt.%, while that of highland plagioclase ranged from 3 to 6.5 wt.%. Xu et al [46] et al determined the FeO abundance threshold of CE-5 landing unit to distinguish pure mare basalt and non-pure mare basalt, that is, 17.2 wt.%. In this paper, pure basalt and mixture are distinguished according to this threshold.…”
Section: Surface Ages Of the Mare Units In The Ce-5 Regionmentioning
confidence: 99%
“…Luna-2, the first hard lander to reach lunar surface, can only perform a transient probe before colliding with the moon. Probers with landing capability are produced to realize surface exploration on the Moon; they usually adopt three or four foldable legs with invert-tripod mechanism, such as Surveyor-1 [2] and Luna-16 [3], or with cantilever mechanism, such as Apollo project [4] and Chang'e 3, 4, and 5 [5][6][7]. For probers with invert-tripod or cantilever mechanism, their leg often consists of a main branch chain and two multifunctional auxiliary branch chains.…”
Section: Introductionmentioning
confidence: 99%